Performance of Hamamatsu VUV4 SiPMs for detecting liquid argon scintillation. (1st April 2022) - Pershing, T.; Xu, J.; Bernard, E.; Kingston, J.; Mizrachi, E.; Brodsky, J.; Razeto, A.; Kachru, P.; Bernstein, A.; Pantic, E.; Jovanovic, I.
Abstract: Detection of light signals is crucial to a wide range of particle detectors. In particular, efficient detection of vacuum ultraviolet (VUV) light will provide new opportunities for some novel detectors currently being developed, but is technically challenging. In this article, we characterized the performance of Hamamatsu VUV4 silicon photomultipliers (SiPMs) for detecting VUV argon scintillation light without wavelength shifting. Using a customized cryogenic amplifier design, we operated two models of VUV4 SiPMs inside liquid argon and thoroughly examined their direct sensitivities to liquid argon scintillation. In addition to describing their cryogenic performance, we measured a photon detection efficiency of 14.7 +1.1 -2.4 % and 17.2 +1.6 -3.0 % at 128 nm for these two VUV4 models for operation at 4 V of overvoltage, with the main uncertainty arising from the SiPM reflectivity for VUV light.